An image processing study of a reentrant discotic cholesteric – biaxial cholesteric phase transition. (3rd April 2018) - Luders, D. D.; Zoner, G. A.; Santos, O. R.; Braga, W. S.; Sampaio, A. R.; Kimura, N. M.; Palangana, A. J.; Simões, M.
ABSTRACT: In this work, we study and characterize the cholesteric sequence of phases ( Ch Dr − Ch B − Ch D ), where the first Ch Dr is the reentrant cholesteric discotic phase, Ch B is the cholesteric biaxial phase and the second Ch D is the cholesteric discotic phase. This sequence of phases is studied through polarized light microscopy and image processing technique, where, for the first time, the domains and borders of these transitions are established and characterized. They are also investigated and optically characterized throughout their textures.